Plato and the Invention of Life - Naas, Michael (Book collections on Project MUSE., 2018)
While the question of life (whether bios or zoe) is not the explicit focus of any Platonic dialogue, it is, this work argues, an absolutely central and structuring question for all of Plato's thought and, perhaps especially, for his ontology.